Corrosion-resistant Cu-Fe-based immiscible medium-entropy alloy with tri-layer passivation. (December 2021) - Moon, Jongun; Choi, Young; Sasaki, Taisuke; Joo, Minho; Shin, Hyunkwon; Lee, Jeong Soo; Ohkubo, Tadakatsu; Hono, Kazuhiro; Baek, Seung Mi; Kim, Hyoung Seop
Abstract: Here, a novel alloy design strategy for improving corrosion resistance of Al15 (CuFeMn)85 (at%) immiscible dual-phase medium-entropy alloy is proposed and verified experimentally. The corrosion resistance of the alloy significantly enhances with the addition of Cr. During the corrosion of the Cr-containing alloy, three different oxide layers of Cu-, Cr-, and Fe-rich oxide layers with a few nm thickness are sequentially formed as a layered structure. Such tri-layer oxide enhances corrosion resistance by shielding the surface of the matrix, and the corrosion resistance of the alloys is comparable to that of austenitic stainless steels. Highlights: The corrosion resistance of Cu-Fe-based immiscible medium-entropy alloys is improved through the addition of Cr. The Cr addition prevents localized corrosion by selectively enhancing the corrosion potential of Fe-rich phase. The tri-layer oxide passivation is associated with the corrosion-resistant characteristic in the present alloys.